Servant leadership, brand love, and work ethic: important predictors of general health in workers in the education sector - Laura-Arias, Elena; Villar-Guevara, Miluska; Millones-Liza, Dany Yudet (Frontiers in Psychology, 2024)
Background: Building a path aimed at the well-being of workers in the education sector is the fundamental basis to encourage quality education. To fill the gap in knowledge and address this aspect by understanding the behavior of the study population, it was proposed as with the objective of determining if servant leadership, brand love and work ethic predict the general health in workers.Methods: A non-probability sampling was applied for convenience. For this purpose, a sample of 509 workers from Peru was submitted to study, who completed a questionnaire consisting of: scale of servant leadership, work ethic, GHQ-12 and brand love. By applying a quantitative method using a structural equation modeling partial least squares approach (PLS-SEM).The present study demonstrated that the three constructs (servant leadership, brand love, and work ethic) predict the general health of workers in a positive and significant way, in a sample of Peruvian workers in the education sector. Furthermore, the results suggest that these factors can be used to improve the health of employees in educational institutions in Peru and possibly in other contexts as well.Given these results and after knowing the solidity of the predictions, the importance of promoting general health in workers in the education sector.